2002
DOI: 10.1002/jcp.10079
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TGF‐α gene knockout on epithelial cell kinetics and repair of methotrexate‐induced damage in mouse small intestine

Abstract: While previous studies have indicated that exogenous TGF-alpha stimulates epithelial growth, maintenance, and repair of the gut, roles of endogenous TGF-alpha are less well-defined particularly in the small bowel. The current study examined effects of TGF-alpha knockout on adult small intestinal epithelial cell proliferation, migration, apoptosis, and damage/repair response after methotrexate treatment. Compared to normal mice, TGF-alpha gene knockout did not affect crypt cell production, mitosis position, mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
3
11
1
Order By: Relevance
“…Growing evidence suggests that cell apoptosis plays a crucial role in this process. Our data showed that programmed cell death is one of the pathways leading to mucosal damage as well as to marked mucosal atrophy observed in half of the animals following MTX administration, and is consistent with data reported by other investigators [18, 19]. Both decreased cell proliferation and increased cell apoptosis suggest a decreased enterocyte turnover, which might explain mucosal hypoplasia after MTX treatment.…”
Section: Discussionsupporting
confidence: 81%
“…Growing evidence suggests that cell apoptosis plays a crucial role in this process. Our data showed that programmed cell death is one of the pathways leading to mucosal damage as well as to marked mucosal atrophy observed in half of the animals following MTX administration, and is consistent with data reported by other investigators [18, 19]. Both decreased cell proliferation and increased cell apoptosis suggest a decreased enterocyte turnover, which might explain mucosal hypoplasia after MTX treatment.…”
Section: Discussionsupporting
confidence: 81%
“…2a and b). This result confirms that MTX has toxic effects on rapidly proliferating crypt epithelial cells (Pinkerton and Milla 1984;Xian et al, 1999;2000;2002;Xian, 2003).…”
Section: Intestinal Mucosal Histopathological Analysissupporting
confidence: 89%
“…Up to now the widely accepted hypothesis on the pathobiology of mucositis includes five phases of mucositis development and resolution: initiation, primary damage response, signal amplification, ulceration and healing (Al-Dasooqi et al, 2013;Crohns et al, 2009;Gilliam and St. Clair, 2011;Il'yasova et al, 2009;Sonis, 2009). Both DNA and non-DNA damages exert on epithelial and submucosal cells following chemotherapy, which cause intricate sequential biological events, such as generation of reactive oxygen species (ROS), transcription factor activation, pro-inflammatory cytokine expression/accumulation, nitrosative stress, cell apoptosis, reduction in epithelial cell proliferation, changes in growth factor expression, proteolysis, bacterial colonization, and activation of enteric immune and nervous systems (Al-Dasooqi et al, 2013;Kolli et al, 2008;Logan et al, 2007;2009;Qutob et al, 2013;Sonis, 2009;Xian et al, 1999Xian et al, , 2000Xian et al, , 2002Xian, 2003;Zhan et al, 2014). Great efforts have been applied to evaluate/ develop interventions that prevent or reduce the toxic effects of chemotherapy, such as intensive oral hygiene care and usage of antiseptics, antimicrobial and anti-inflammatory agents, cytokines, growth factors, antioxidants, immune modulators and homeopathic agents (McCulloch et al, 2014;Nadhanan et al, 2013;Qutob et al, 2013;Rodríguez-Caballero et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Ninety minutes prior to sacrifice, rats were i.p. injected with 5 0 -bromo-2 0 -deoxyuridine (BrdU) (Sigma, NSW, Australia) at 50 mg/kg for cell proliferation study (Xian et al, 2002. Both hind limbs were dissected.…”
Section: Animal Trials and Specimen Collectionmentioning
confidence: 99%